The models and algorithms for interaction of software agents (International Journal of Mathematics and Physics, 2016)
In this paper software agents' communication models and algorithms in the virtual business environmenthave been proposed. They allow to reduce response time on any changes of environment imitating the innovation field due to increase of data exchange between the agents and reduction of general network load. Two mechanisms for conversion of inter-node agent communications to intra-node agent communications and dynamic agent distribution have been represented. Various implementation approaches for agent communication and interaction mechanisms have been considered. Methods for effectiveness increase of data exchange between mobile agents in the distributed system for information support of innovations have been proposed. Data exchange mechanisms between software agents in the virtual business environment based on agent address structure extension and using of middle-agents brokering and matchmaking services have been minutely described.   GMT АнглийскийИспанскийИтальянскийКазахскийКитайский ТрадКитайский УпрКорейскийРусскийТурецкийФранцузский АнглийскийИспанскийИтальянскийКазахскийКитайский ТрадКитайский УпрКорейскийРусскийТурецкийФранцузский        Звуковая функция ограничена 200 символами  Настройки : История : Обратная связь : DonateЗакрыть